(untitled) (Palíndromo, 2014)
Herein we present a proposal to read images from illustrated books associated with the reading of artistic manifestations, focusing on visual training at school. It is taken as a tool for reading the model developed by Ramalho and Oliveira (2005), which is based on Greimas Semiotics by deconstructing and re-elaborating images to and explore its meanings. As a way of testing this proposal, we propose a short exercise to read illustrations from Rebecca Dautremer’s Diario Segreto di Pollicino (2010), related to the perspective of Art in Post-Production, according to characteristics raised by Bourriaud (2009).